Study of maternal and perinatal outcome of caesarean delivery in late first stage and second stage of labour - Bhatia, Shweta; Revankar, Vijaya M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Second-stage caesarean sections are known to be associated with increased maternal and perinatal complications as compared to late first stage caesarean sections. The objective of the study was to evaluate the maternal and perinatal outcome of caesarean deliveries in the late first stage and second stage of labour. Methods: The prospective observational study of caesarean deliveries done in the late first stage (~8 cm of cervical dilatation) and second stage of labour was conducted at Lady Goshen Hospital, Mangalore and Kasturba Medical College Attavar, Mangalore from August 2018 to June 2020. Comparison of maternal and perinatal outcomes were assessed in late first stage and second stages of caesarean delivery. Results: In the present study intraoperative complications such as extensions of uterine incisions, atonic PPH and bladder base injury and post-operative complications like need for blood transfusion, febrile morbidity and prolonged catheterisation were found more in second stage of labour. Perinatal complications such as hyperbilirubinemia and respiratory distress were found to be more in second stage of labour. Conclusions: As caesarean deliveries are increasing, it is better to make an institutional protocol regarding duration of second stage of labour, use of instrumental delivery to guide us about timely intervention (operative vaginal/caesarean) in advanced labour, thereby aiming to reduce the maternal and perinatal complications.